The complex polyploid genome architecture of sugarcane - Healey, A L; Garsmeur, O; Lovell, J T; Shengquiang, S; Sreedasyam, A; Jenkins, J; Plott, C B; Piperidis, N; Pompidor, N; Llaca, V; Metcalfe, C J; Doležel, J; et al. (Nature, 2024)
Sugarcane, the world's most harvested crop by tonnage, has shaped global history, trade and geopolitics, and is currently responsible for 80% of sugar production worldwide1. While traditional sugarcane breeding methods have effectively generated cultivars adapted to new environments and pathogens, sugar yield improvements have recently plateaued2. The cessation of yield gains may be due to limited genetic diversity within breeding populations, long breeding cycles and the complexity of its genome, the latter preventing breeders from taking advantage of the recent explosion of whole-genome sequencing that has benefited many other crops. Thus, modern sugarcane hybrids are the last remaining major crop without a reference-quality genome. Here we take a major step towards advancing sugarcane biotechnology by generating a polyploid reference genome for R570, a typical modern cultivar derived from interspecific hybridization between the domesticated species (Saccharum officinarum) and the wild species (Saccharum spontaneum). In contrast to the existing single haplotype ('monoploid') representation of R570, our 8.7 billion base assembly contains a complete representation of unique DNA sequences across the approximately 12 chromosome copies in this polyploid genome. Using this highly contiguous genome assembly, we filled a previously unsized gap within an R570 physical genetic map to describe the likely causal genes underlying the single-copy Bru1 brown rust resistance locus. This polyploid genome assembly with fine-grain descriptions of genome architecture and molecular targets for biotechnology will help accelerate molecular and transgenic breeding and adaptation of sugarcane to future environmental conditions.
Keywords: Chromosomes, Plant; genom rostlinný; chromozomy rostlin; Haplotypes; Reference Standards; haplotypy; polyploidie; biotechnologie; Plant Breeding; šlechtění rostlin; hybridizace genetická; referenční standardy; DNA rostlinná; DNA, Plant; Hybridization, Genetic; Genome, Plant; Biotechnology; Saccharum; Polyploidy